2022
DOI: 10.1111/ajd.13822
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid: Its incidence, mortality and clinical outcome in New Zealand

Abstract: Background/objectives Bullous pemphigoid (BP) is an uncommon autoimmune bullous disorder, with significant morbidity and mortality. Mortality may be as high as 23.5% in the first year after diagnosis. Clear epidemiologic data across Australasia are lacking. Methods A retrospective, multi‐centred cohort study was designed to determine the incidence and mortality of bullous pemphigoid in New Zealand. Data from all histopathologically diagnosed patients with bullous pemphigoid between 2009 and 2015 from the Auckl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In this meta-analysis, we found that BP was associated with higher odds of all-cause dementia in middle-aged and older participants in both case-control and cohort studies. This finding is consistent with previous studies that reported an increased risk of dementia in patients with BP [ 1 , 2 , 8 ]. The possible mechanisms underlying this association are not fully understood, but some hypotheses have been proposed.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this meta-analysis, we found that BP was associated with higher odds of all-cause dementia in middle-aged and older participants in both case-control and cohort studies. This finding is consistent with previous studies that reported an increased risk of dementia in patients with BP [ 1 , 2 , 8 ]. The possible mechanisms underlying this association are not fully understood, but some hypotheses have been proposed.…”
Section: Discussionsupporting
confidence: 94%
“…We aligned our inclusion and exclusion criteria with the PICO framework, which is a commonly used tool for framing systematic review research questions and developing literature search strategies. We included studies that: (1) were cohort, case-control, or cross-sectional in design; (2) reported quantitative data on the risk of cognitive outcomes in BP patients compared to a control group of non-bullous pemphigoid patients; (3) provided the effect size estimates HRs or ORs and their 95% CI; and (4) were published in English. We excluded studies that: (1) did not measure cognitive outcomes; (2) did not have a control group; (3) did not provide sufficient data for meta-analysis; (4) were case reports, reviews, meta-analyses, letters, editorials, or commentaries; or (5) had a quality score of less than 4 according to the Newcastle-Ottawa Scale (NOS).…”
Section: Inclusion Criteria and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic Bullous pemphigoid (IBP) is an uncommon autoimmune bullous disorder, with significant morbidity and mortality. It has an incidence rate of 3/100,000 person-years yet a high mortality at 23.5% in the first year after diagnosis [1]. It is predominantly a disease of the elderly, and is associated with significant health care costs [2].…”
Section: Introductionmentioning
confidence: 99%